Early days at York Factory [electronic resource] - Willson, Beckles, 1869-1942. ([Toronto? : s.n.], 1899)
From: The Canadian Magazine, vol. XIII, May, 1899, no. 1. Caption title. Electronic reproduction. Mode of access: Internet. 44